Social capital and corporate cash holdings - Habib, A.; Hasan, Mostafa (Elsevier, 2017)
© 2017 Elsevier Inc. In this paper we investigate the impact of regional social capital on corporate cash holdings. We also examine the possible channels through which social capital may affect cash holdings. Using US data, this study shows that firms from a high social capital county hold significantly less cash than firms from a low social capital county. We also confirm that social capital reduces cash holdings via the financial constraints and financial reporting quality channels, while it increases cash holdings via the systematic and idiosyncratic risk channels. Additional analysis reveals that, the effect of social capital on cash holdings is more pronounced for less geographically dispersed firms. These results are robust to alternative specifications of cash holdings and social capital, and to the use of a two-stage least squares (2SLS) analysis to alleviate the endogeneity concern. Overall, our findings suggest that regional social capital plays an important role in determining corporate cash holdings.